Rare Occurrence of Novel Covid-19 Infection in a patient of Dengue Fever being Treated With Phytochemicals In A Herbal Extract (Kahwa) of Camellia Sinensis in a Developing Country - Bashir, Muhammad Nauman; Bhutta, Musharaf; Adil, Maham Leeza; Mannan, Muhammad Shaheer; Shabbir, Haroon; Gondal, Soban Sarwar (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: The concurrence of an epidemic and a pandemic is a harsh reality in numerous developing countries around the world. As the entire world suffers from the novel coronavirus (SARS COV-2) pandemic, many areas of the world have had the added burden of endemics that are equally burdensome as the current pandemic. Case Presentation: In our report, we presented a case in Pakistan of a 28-year-old patient suffering from Dengue fever who also contracted COVID-19 and was subsequently treated conservatively along with oral intake of polyphenols present in the traditional herbal extract from Camellia sinensis plant & inhalational steam following which he tested negative. To date, such cases have only been reported extremely rarely even in Pakistan. Our study highlights the plausible effect of the herbal extracts of Camellia species in treating the Covid-19 infection and halting its progression. Discussion: This case study highlights the significance of extracting, purifying and pharmacologically testing those specific phytochemical compounds in the Camellia herbs that have the potential therapeutic properties effective against respiratory viral illnesses, in particular, COVID-19, and can prove to be effective treatment modalities in the future. Polyphenols are active substances against various types of viral infections. Researchers have characterized methods of how to isolate polyphenols without losing their potential to formulate pharmaceutical products. Researchers have also described mechanisms against common viral infections (i.e., influenza, herpes, hepatitis, rotavirus, coronavirus). Our work also paves the way for future interventional research to elucidate the plausible interactions between the pathophysiology of these two viral illnesses and the resultant effects on their prognosis. Since both Flavivirus and SARS-COV-2 are enveloped, single, positive-stranded RNA viruses, there is a significant possibility of interaction between their pathogenesis at the molecular level, which can translate into a wide range of clinical outcomes, when these infections concur. Particularly our case study reflects upon the alleviation of Covid-19 symptoms in the concurrent setting of dengue. This case report emphasizes the importance of rigorous clinical testing of polyphenol extracts of all Camellia species for possible novel Anti-viral drugs. Moreover, our study also depicts the alarming situation of two epidemics happening simultaneously which imposes an exponential burden on an already overburdened healthcare system in the third world and draws attention towards medical legislation by health ministries & pre-emptive readiness of infectious disease specialists in case of an emergency outbreak.